Adoção internacional: a realidade em Goiás na efetivação do direito da criança à família. - Lucena, Kenia Cristina Ferreira de Deus (2014)
This thesis is part of the Research Line Socio- Economic Relations . Has as main objective to know the institute of international adoption and its implementation in the State of Goiás earch The problem is mainly geared subsidiary nature and exceptional mandated by law to matters of international adoption. Specific objectives : analyzes the Law 12.010 of 2009 and its consequences for the process of transnational adoption , identifies the advantages and disadvantages of international adoption , and whether this type of adoption is an option to alleviate the problem of abandonment of children in Goiás , we study a specific case of international adoption in Goiânia to see the benefits and possible difficulties of the adoptee . We opted for the dialectical method as a methodological option to conduct investigative work and bibliographic and documentary survey . Research proved that Brazil has to want to adopt a profile in mind of a child: white , up to three years old. Because of this , many abandoned children who do not fit this profile are deprecated in shelters , day after day reliving his rejection . One option to solve the problem of abandonment of these children would intercountry adoption today an office authorized in exceptional cases and subsidiary national adoption. Thus , it is suggested a debate , to demonstrate that the primary is to provide a home for these little abandoned , encouraging adoption by foreigners as much as it encourages the adoption by national.